Ann Based Novel Approach To Detect Node Failure In Wireless Sensor Network - Sundresan A/L Perumal; Mujahid Tabassum; Ganthan Narayana; Suresh Ponnan; Chinmay Chakraborty; Saju Mohanan; Zeeshan Basit; Mohammad Tabrez Quasim (Computers, Materials & Continua, 2024)
Indexed by WOS/Scopus/ERA